Metabolic syndrome and its components in Polish women of childbearing age: a nationwide study - Dorota Szostak-Węgierek; Anna Waśkiewicz; Walerian Piotrowski; Urszula Stepaniak; Andrzej Pająk; Magdalena Kwaśniewska; Paweł Nadrowski; Arkadiusz Niklas; Aleksandra Puch-Walczak; Wojciech Drygas (BMC, 2017)
Abstract Background Abnormal body mass and related metabolic disorders may affect female reproductive health. The purpose of the study was to determine the prevalence of underweight, overweight, obesity, lipid and glucose metabolism disorders, hypertension, and metabolic syndrome, among Polish women of childbearing age. Methods One thousand five hundred eighty-eight non-pregnant Polish women of childbearing age (20-49 years) who participated in the Multi-Centre National Population Health Examination Survey (WOBASZ II study) in 2013-2014, were assigned to 3 age groups: 20-29 years (n = 403), 30-39 years (n = 600) and 40-49 years (n = 585). Measurements of weight, height, waist circumference, blood pressure, blood lipids, and blood glucose were taken. For statistical analysis, the Kruskal-Wallis, Chi-Square, and Cohran-Armitage tests were used. Results Of the participants, 4.3% were determined to be underweight, 25.2% were overweight, 15% were obese, and 53.1% had abdominal obesity. With age, the prevalence of both excessive body mass and abdominal obesity tended to increase, and that of underweight to decrease. Frequency of hypercholesterolemia and hypertriglyceridemia found in the whole group were 50% and 12.6% respectively, and also tended to rise with age. Low serum HDL-cholesterol (high density lipoprotein cholesterol) levels were found in 15.1% of the participants. Prevalence of impaired fasting glucose in the whole group was 8.2% and tended to increase with age. Diabetes was found in 1.2% of the participants and its prevalence also tended to rise with age, at the borderline of significance. Frequency of arterial hypertension and metabolic syndrome in the whole group was 15.7% and 14.1% respectively and both tended to increase with age. Conclusions Overweight and obesity, especially of abdominal type, and the related metabolic abnormalities are common in Polish women of childbearing age. Their prevalence tends to increase with age. Underweight is relatively common in the youngest age group.